Kemampuan Tingkat Gender Siswa Terhadap Hasil Belajar Kewirausahaan Kelas X II Sma Negeri 1 Ketapang Kalimantan Barat - Fitria Sari Hasanusi (Peneliti.net, 2019)
The purpose of the study was to analyze the relationship between gender level reasoning abilities towards students' mathematics learning outcomes, the type of quantitative research. The population of this research was 98 students in class XII of Ketapang 1 Public High School, West Kalimantan. The research sample was 98 students based on Arkunto's income. Data collection techniques with questionnaires and documentation. The data analysis technique uses correlation analysis. The results of the study are known 1) There is no difference in mathematical learning reasoning abilities, between male students and female students in terms of learning outcomes, 2) There is no relationship between gender level reasoning skills in mathematics learning with student learning outcomes.